Risk exposure and acquisition of macroeconomic information - Christopher Roth; Sonja Settele; Johannes Wohlfahrt (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
We conduct an experiment with a representative sample from the US to study households' demand for macroeconomic information. Respondents who learn of a higher personal exposure to unemployment risk during recessions increase their demand for an expert forecast about the likelihood of a recession. This finding is consistent with macroeconomic models of endogenous information acquisition, according to which the demand for information depends on its expected benefits. Moreover, respondents' updating about their personal unemployment risk suggests that households are imperfectly informed about their exposure to aggregate fluctuations, which may distort their beliefs about the benefits of acquiring macroeconomic information.
Keywords: D12; D14; D83; D84; E32; G11; 330; Risk Exposure; Macroeconomic Conditions; Information Acquisition; Experiment